2020
DOI: 10.5812/ijp.86281
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian Version of IMPACT-III Quality of Life Questionnaire in Iranian Children with Inflammatory Bowel Disease

Abstract: Background: Inflammatory bowel diseases (IBD) can adversely affect children in many different ways. Health-related quality of life (HRQOL) involves all aspects of life quality, along with physical or mental perceptions of health, which could exert an overall effect on an individual's health. The IMPACT-III questionnaire is a well-established and validated tool for evaluation of the HRQOL in children with IBD. Objectives: The objective of this work was to translate this tool into Persian so it could be utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Positive results for secondary outcomes were reported in 6 studies, including reduced serum levels of nitric oxide metabolites or rectal NO production (11,16); decreased hospital admissions (17); improved quality of life (20,22); and positive changes in the intestinal microbiota (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive results for secondary outcomes were reported in 6 studies, including reduced serum levels of nitric oxide metabolites or rectal NO production (11,16); decreased hospital admissions (17); improved quality of life (20,22); and positive changes in the intestinal microbiota (23).…”
Section: Resultsmentioning
confidence: 99%
“…The 9 studies included in this systematic review (Bruzzese et al, 2004 (16), Bruzzese et al, 2007 (17), Weiss et al, 2010 (18), Fallahi et al, 2013 (19), Del Campo et al, 2014 (20), Di Nardo et al, 2014 (21), Jafari et al, 2013 (22), Bruzzese et al, 2014 (23), Bruzzese et al, 2017(12), and de Freitas et al, 2017 (11)) are described in Table 1 part A. The study excluded from the analysis is also described in Table 1 part B: Infant Pina et al, 2008 (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean total IMPACT-III score from current cohort was 68.44. A recent study by Jafari et al 22 on the HRQoL of 89 Persian children reported mean total IMPACT-III score of 57.11. The score was much lower as compared to our study likely contributed by the larger proportion of children with active disease (46%) compared to our study (33.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The mean total IMPACT‐III score from current cohort was 68.44. A recent study by Jafari et al 22 . on the HRQoL of 89 Persian children reported mean total IMPACT‐III score of 57.11.…”
Section: Discussionmentioning
confidence: 99%